Operational Training Management System (OPTRAMS) for safe operation in process plant - Aziz, H.A. (Trans Tech Publications Ltd, 2014)
Many publications have reported about 37 of major accidents in petroleum, chemical, nuclear, aviation, and in the other process industries that occurred worldwide were due to human error. One of the keys contributing factors that could prevent these accidents is to provide appropriate training to the plant personnel. However, accidents still can happen if training is poorly managed and improperly trained personnel handling the operation of the plant. One of the established industrial standards to manage the training is Training element of Process Safety Management (PSM) 29 CFR 1910.119(g). This paper presents a system to manage training for safe operation following 29 CFR 1910.119(g) namely Operational Training Management System (OPTRAMS). It provides strategies to manage information and documentation related to training. OPTRAMS was implemented at the CO2-Hydrocarbon Absorption System (CHAS) pilot plant at Universiti Teknologi PETRONAS as a case study. The study showed that all operational training can be managed efficiently with OPTRAMS and also assists end users to identify the gaps that hinder training of PSM compliance. The implementation of this technique could help end users to prevent and minimize catastrophic accidents and comply with training of PSM standard. Â© (2014) Trans Tech Publications, Switzerland.